The effect of pecking order, trade-off and market timing theories on capital structure in commercial banking companies listed on IDX - Laely Aghe Africa; Avi Sunani (STIE Perbanas Surabaya, 2017)
Capital structure has an impact on the short and long term. Funding provided by banks is inseparable from the availability of funds from third parties in the form of savings, demand deposits and deposits. The entry of third party funds must be balanced with the funds disbursed by the company. Therefore, management policy greatly determines the position and composition of funding. This study aims to analyze and determine several capital structure theories, namely Pecking Order Theory, Trade-Off Theory and Market Timing Theory. The variable of Pecking Order Theory is represented by funding deficit, long-term debt, and total debt. The variable of Trade-Off Theory is represented by tangi-ble assets, growth, size, profitability, total debt, and long-term debt. The variable of Mar-ket Timing Theory is represented by Equity Finance Weighted Average of market to book ratio and leverage ratio. This research is quantitative research. The samples used in this study are 100 data of commercial banking companies listed on IDX period 2011 - 2015. Data are obtained using purposive sampling method from banks registered at www.idx.go.id. Multiple Liner Regression is used in analyzing data using SPSS IBM 23. The results of the research show that Trade-Off and Market Timing Theories can be implemented by banking companies in terms of determining capital structure. This re-search implication is to enhance management choices, especially on how to set capital structure of the company.